Formulasi dan Evaluasi Lipstik Berbasis Parafin Solid serta Lanolin sebagai Emolien dan Penstabil - Citra Bunga Lestari; Amraini Amelia (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study aims to design and evaluate lipstick preparations by utilizing solid paraffin as the base ingredient and lanolin as an emollient and stabilizer. Solid paraffin was chosen because of its dense properties at room temperature and having the ability to form a stable lipstick structure. In addition, paraffin can provide a smooth, durable surface, and provide good smearing power. On the other hand, lanolin is known as a natural emollient ingredient that functions to moisturize and protect the lips from dryness. Lanolin also has water-retaining properties (occlusive) so that lip moisture is maintained even if the lipstick is used for a long time. The process of making lipstick is carried out by the melting method using indirect heating to maintain the stability of the material and prevent color and aroma degradation. All materials are accurately weighed, then put into beaker glass and heated over three legs using a Bunsen lamp. During heating, the ingredients are gently stirred so that all the components, including solid paraffin and lanolin, melt and mix homogeneously. Once the mixture reaches the desired consistency, the formula is poured into the lipstick mold and allowed to set at room temperature until ready for use. The results of the evaluation test showed that the combination of solid paraffin and lanolin was able to create lipstick with an optimal solid texture, even color, not easy to crack, and had a smooth application power on the surface of the lips. Lanolin plays a big role in providing a soft, moisturizing effect and adding a natural shine to the lips. Meanwhile, solid paraffin helps maintain the shape of the lipstick so that it doesn't break easily when applied. This study also highlights the importance of comparing the composition of ingredients to produce lipsticks that have a stable melting point, good application power, and appropriate adhesion.